PENINGKATAN KESADARAN REMAJA TERHADAP BAHAYA PERNIKAHAN DINI, PERGAULAN BEBAS DAN PENTINGNYA KESEHATAN REPRODUKSI SEBAGAI UPAYA PENCEGAHAN HIV/AIDS MELALUI SOSIALISASI INTERAKTIF DI MTSS AL-FATHU KELURAHAN MEKARSARI, KECAMATAN PULOMERAK, KOTA CILEGON - Afriani, Raden Irna; Hakim, Muhamad Zidan; Rustandi, Tata; Mardianti, Siti; Febriyanti, Afi Nurul; Rohmadona, Awanda; Nurfitriana, Rian (Yayasan Education and Social Center, 2025)
The rise in cases of risky adolescent behavior and the lack of understanding regarding reproductive health have become contributing factors to the increasing spread of HIV/AIDS among young people. This community engagement activity aims to raise adolescents’ awareness of the dangers of promiscuity and the importance of maintaining reproductive health as a preventive measure against HIV/AIDS. The interactive socialization was conducted at MTSS AL-FATHU, located in Mekarsari Sub-district, Pulomerak District, Cilegon City, using a participatory approach involving group discussions, educational video screenings, case simulations, and Q&A sessions. The participants were junior high school students aged 12–15 years. The results showed an increase in students’ knowledge and understanding of the negative impacts of promiscuity and the significance of early reproductive health awareness. This program received positive responses from both students and school staff, who expressed interest in similar initiatives being conducted regularly. Therefore, interactive socialization proves to be an effective method in shaping adolescent awareness and positive attitudes toward reproductive issues and HIV/AIDS prevention.